PENDAMPINGAN BELAJAR DAN CERDAS CERMAT SISWA SD DI DESA PRASUNG KECAMATAN BUDURAN - Dewi Sukriyah; Siti Nuriyatin (STKIP PGRI Sidoarjo, 2022)
Thematic KKN in Prasung Village is divided into several Posdaya including health Posdaya, Environmental Posdaya, Arts and Culture Posdaya, Economic Posdaya, Education Posdaya, and Religious Posdaya. The most prominent Posdaya is the Education Posdaya. This is because the program created has a positive impact on local residents, especially elementary school students in Prasung. The main target of this activity is elementary school students in Prasung Village. It aims to assist parents in assisting their children's learning and increasing their learning motivation. This activity is carried out in 3 stages. In the first stage, observations were made on the target of the activity program to determine the appropriate method for the target conditions and situations. In the second stage, tutoring held for 4 weeks. At the last stage, a quiz competition was held. The results of this activity are that children understand the lessons at school more, children become more enthusiastic, confident, and happy to learn, this activity can help parents in children's learning activities.